Interfacial Characterization of Graphene Oxide and Carbon Nanotubes-Strengthened Aluminium Matrix Composites - Dr. K. Fazlur Rahman; Praveen B.M (International Journal of Scientific Research in Science and Technology, 2024)
Fast innovations and improvements in the manufacturing sector continuously demand new and reliable materials to create higher quality goods faster. Metal matrix composites (MMCs) are one of the most conspicuous materials to achieve vital jobs in the manufacturing industry. They are growing as critical materials owing to their unique properties, such as higher strength, superior abrasion and wear resistance, and lower constants of thermal enlargement while maintaining greater corrosion resistance. Aluminium (Al) matrix composites (AMCs) are the most important candidates to fabricate intricate shapes of apparatus in different sectors such as aerospace, automobile, and marine industries. On the other hand, its poor hardness and decreased abrasion resistance have limited its application in some crucial engineering sectors. On the other hand, carbon nanomaterials, including graphene oxide (GO) and carbon nanotubes (CNTs) are considered excellent reinforcement nanomaterials for strengthening AMCs. In this research, we add 0.5 wt. % GO or 0.5 wt. % CNTs to strengthen the AMC. This study fabricates the composites through the powder metallurgical method. This study conducts different analyses related to texture, chemical structure, porosity, interface and reinforcement structure, and Electron Backscatter Diffraction (EBSD) of developed composites. EBSD is used to determine the local crystal configuration and crystal orientation at the surface of a specimen. Pole figure maps are used to analyze the texture of the developed composite specimen. The Al/0.5 wt. % GO material demonstrated a more enhanced surface morphology than pure Al sample owing to the restraining properties of GO, which led to better mechanical characteristics. While, the Al/0.5 wt. % CNT material possessed the equal average particle size as the pure Al sample and revealed a reduced engineering stress. This phenomenon was characterized by a lower performance of load transfer from the Al material to the strengthening materials, due to the deficiency of chemical reactions at the boundaries and the extensive agglomeration of the carbon nanotubes.
Keywords: Aluminium matrix composites; carbon nanotubes; chemical structure; graphene oxide; texture; pole figure; reinforcements